Tranexamic Acid Use in Foot and Ankle Surgery. Issue 4 (15th December 2020) - Johns, William L.; Walley, Kempland C.; Seedat, Raees; Jackson, Benjamin; Boukhemis, Karim; Gonzalez, Tyler
Background: There is a potential role for tranexamic acid (TXA) use in foot and ankle procedures; however, the benefits of this intervention have not been fully elucidated. The purpose of this study was to explore the safety, outcomes, and medical complication profile of the use of intravenous TXA in patients undergoing foot and ankle surgery. Methods: A prospective study with retrospective review of 241 patients undergoing elective and traumatic foot and ankle procedures was performed. One gram of intravenous (IV) TXA was administered prior to incision. Patients were followed and evaluated for medical comorbidities, intraoperative blood loss, wound complication, superficial and deep infections, hematoma formation, medical complications, 30-day hospital readmission rate, and return visits to the emergency department or urgent care setting prior to first postoperative visit. Descriptive statistics were used for subgroup analysis. Mean postoperative follow-up was 4.5 months. Results: Estimated blood loss in all cases was less than 20 mL. There was 1 case of superficial cellulitis (1/241, 0.4%), 1 deep infection after Achilles tendon repair (1/241, 0.4%), 4 cases of delayed wound healing (4/241, 1.6%), 1 instance of deep vein thrombosis (1/241, 0.4%), and 2 cases of postoperative pulmonary embolism (2/241, 0.8%). There were no instances of postoperative hematoma formation. There were no additional recorded thromboembolic events. There were no adverse drug reactions. There were no 30-day hospital readmissions or return visits to the emergency department or urgent care setting before the first postoperative visit. In a subgroup analysis, there was no significant difference in wound complications or infections between nondiabetics and diabetics ( P > .05) and traumatic and nontraumatic cases ( P > .05). Conclusions: The use of IV TXA in foot and ankle surgeries was associated with low risk of wound complications, infections, hematoma formation, thromboembolic events, and overall complication rates with minimal side effect profile. Perioperative tranexamic acid use may prove to be beneficial in foot and ankle surgery patients but especially in higher-risk patients such as those with diabetes, trauma, and those that are immunocompromised. Level of Evidence: Level IV, case series.